Neurofeedback strategies in binge-eating disorder as predictors of EEG-neurofeedback regulation success - Wimmer, Jytte; Rösch, Sarah Alica; Schmidt, Ricarda; Hilbert, Anja (Frontiers in Human Neuroscience, 2023)
Treatment options such as neurofeedback (NF) that directly target the link between aberrant brain activity patterns and dysfunctional eating behaviors in binge-eating disorder (BED) are emerging. However, virtually nothing is known about mental strategies used to modulate food-specific brain activity and the associated brain-based or subjective success of specific strategies. This study firstly investigated the use of mental strategies in response to individually appetitive food cues in adults with BED and overweight or obesity based on a randomized-controlled trial providing electroencephalography (EEG)- or functional near infrared spectroscopy (fNIRS)-NF to BED. Strategy reports written by participants were classified with qualitative content analysis. Additionally, the mental strategies employed by the N = 23 patients who received EEG-NF targeting the reduction of fronto-central high beta activity were analyzed quantitatively through their link with subjective and EEG-NF regulation success. The following eight categories, ordered by frequency in descending order, were found: “Behavior,” “Imagination,” “Emotion,” “Distraction,” “Thought,” “Concentration,” “Self-Talk” and “No Strategy.” Linear mixed models revealed “Imagination,” “Behavior,” and “Thought” strategies as positive predictors of EEG-NF regulation success (defined as high beta activity during regulation beneath the baseline), and “Concentration” as a negative predictor of subjective NF regulation success (i.e., self-reported). In conclusion, our study offers a classification system that may be used in future studies assessing strategy use for regulating food-related responses in patients with BED and associated overweight/obesity, providing valuable information on potential benefits of specific strategies and transferability to situations outside the NF treatment.